2021
DOI: 10.2147/opth.s306706
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Disputes About Curcumin in Retinal Diseases

Abstract: Curcumin belongs to the group of so-called phytocompounds, biologically active molecules produced by plants exerting a beneficial effect on health. Curcumin shows a wide spectrum of different properties, being an anti-inflammatory, antioxidant, antimicrobial and antimutagenic molecule. The purpose of the review is to examine what literature reported on the characteristics of curcumin, particularly, on the beneficial and controversial aspects of this molecule, aiming for a better therapeutic management of retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 128 publications
(142 reference statements)
0
19
0
Order By: Relevance
“…Most retinal diseases, as already mentioned, imply abundance of ROS and reduced levels of scavenger antioxidants. In particular, RGC and photoreceptors are extremely sensitive to oxidative stress damage and it is known that the accumulation of ROS is often involved in several diseases of the retina, such as uveitis, age-related macular degeneration, diabetic retinopathy, retinal tumors and proliferative vitreoretinopathy (PVR) [135]. In order to know the effect of curcumin after an oxidative stress insult, Munia et al, have shown that this nutraceutical compound was capable of protecting human retinal epithelial cells from death [136].…”
Section: Curcumin and Quercetinmentioning
confidence: 99%
“…Most retinal diseases, as already mentioned, imply abundance of ROS and reduced levels of scavenger antioxidants. In particular, RGC and photoreceptors are extremely sensitive to oxidative stress damage and it is known that the accumulation of ROS is often involved in several diseases of the retina, such as uveitis, age-related macular degeneration, diabetic retinopathy, retinal tumors and proliferative vitreoretinopathy (PVR) [135]. In order to know the effect of curcumin after an oxidative stress insult, Munia et al, have shown that this nutraceutical compound was capable of protecting human retinal epithelial cells from death [136].…”
Section: Curcumin and Quercetinmentioning
confidence: 99%
“…The superficial capillary plexus (SCP) is primarily located within the ganglion cell layer. A significant reduction in SCP vessel density has been found in the loss of ganglion cells [39] . We found that SCP flow density was inversely associated with FLV in a proportion of patients with CCSC and RCSC.…”
Section: Discussionmentioning
confidence: 96%
“…The oral administration of curcumin can relieve chronic diabetic macular edema and improve visual acuity [259]. The above reports demonstrate the therapeutic value of natural antioxidants in ophthalmic diseases [248,260].…”
Section: Natural Antioxidant Therapy For Oxidative Stress-related Eye...mentioning
confidence: 99%